Determinan Efektivitas Praktik Kerja Lapangan di SMK: Systematic Literature Review Berbasis PRISMA 2020 dalam Konteks Kurikulum Merdeka - Armen; Ambiyar; Maksum, Hasan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Field Work Practice (PKL) is now formally established as a subject in Indonesia's Merdeka Curriculum under Permendikdasmen No. 13/2025 and BSKAP Decree No. 046/H/KR/2025. A persistent paradox between strengthening regulations and a vocational school (SMK) open unemployment rate of 8.63% (BPS, February 2025) justifies the urgency of a systematic review. Purpose: To map and synthesize empirical evidence on determinants of PKL effectiveness at SMK (2015-2025) and propose an Input-Process-Output conceptual model. Method: Systematic Literature Review (SLR) with PRISMA 2020 protocol; from 502 records across Google Scholar, GARUDA, and SINTA, 50 articles were included via thematic synthesis (Thomas & Harden, 2008); quality was assessed using an adapted CASP instrument; inter rater agreement κ=0.84 (substantial agreement). Findings: Six themes emerged. PKL consistently and positively influences work readiness (single model β=0.42-0.55; r=0.59-0.67). Effectiveness is conditional upon five critical factors within an Input-Process-Output framework. The phenomenon of “ceremonial PKL” (formal but non substantive placements) was identified in ≥3 studies as a systemic threat. Contribution: This article proposes an original IPO based Conditional Model of PKL Effectiveness that explicitly integrates Merdeka Curriculum policy dimensions and Indonesia's structural conditions distinguishing it from generic IPO models. The model links planning quality, partnership intensity, supervision quality, competency alignment, and assessment authenticity as a policy framework for PKL.